Pediatric Pes Planus (flatfoot) - Burak Kaymaz (SERNEV, 2022)
Flatfoot (pes planus) is described as a reduction or absence of the medial longitudinal arch (MLA) of the foot, with or without additional deformities of the foot and ankle. It is a very common orthopedic manifestation in infants and children and usually resolves by adolescence. Flat foot is usually flexible and painless with no functional compromise so that described as physiologic. In some rare cases flatfoot can become painful or rigid and may be a sign of pathology such as vertical talus or tarsal coalition. Although it is very common, there is no standard definition and no universally accepted classification system for pediatric flatfoot. Furthermore there are no large, prospective studies comparing the natural history of flatfoot in response to various treatments during the developmental period. Current literature suggests that it is safe and appropriate to simply observe an asymptomatic child with flatfoot. Painful flexible flatfoot may benefit from orthopedic intervention such as physical therapy, orthosis or sometimes a surgical procedure.Keywords: Pes planus, flatfoot, infant, child, foot arch, surgery